Israel : Detailed Assessment of Observance of Basel Committee on Payments and Settlement Systems Core Principles for Systemically Important Payment Systems. (IMF Staff Country Reports; Country Report ;, 2012)
This paper presents detailed assessment of Israel's compliance with Basel Committee on Payments and Settlement Systems Core Principles for Systemically Important Payment Systems. A significant improvement in the payments landscape has been noted, with the high value payment system meeting most international standards. Together with the creation of the Zahav system, as part of the reform in the payment and settlement systems, the Bank of Israel has also introduced a series of other changes and improvements into the existing payments systems, to bring them into line with accepted international standards.